Ответы и объяснения

Лучший Ответ!
2014-01-15T12:07:50+00:00
Б) Выражение: (1-2*x)*(1-3*x)=(6*x-1)*x-1
1. 1-5*x+6*x^2-(6*x-1)*x+1=0
2. 1-5*x+6*x^2-(6*x^2-x)+1=0
3. 1-5*x+6*x^2-6*x^2+x+1=0
4. 1-5*x+x+1=0
5. 1-4*x+1=0
6. 2-4*x=0
Решаем относительно x: x=-(-2)/4=2/4=1/2=0.5.
Ответ: 0,5; 
в)  
Выражение: 12-x*(x-3)=(6-x)*(x+2)
1. 12-x^2+x*3-(6-x)*(x+2)=0
2. 12-x^2+x*3-(4*x+12-x^2)=0
3. 12-x^2+x*3-4*x-12+x^2=0
4. 12-x^2-x-12+x^2=0
5. -x^2-x+x^2=0
6. -x=0
Ответ: 0;
г) Выражение: (x+4)*(x-1)=x-(x-2)*(2-x)
1. x^2+2*x-4+(x-2)*(2-x)=0
2. x^2+6*x-4-x^2-4=0
3. 6*x-4-4=0
4. 6*x-8=0
Решаем относительно x: x=8/6=4/3
Ответ: 
4/3